Herkes İçin Spor ve Wellness Araştırmaları 3 - Öztürk, Mehmet Ali; Tetik Dündar, Sibel; Beşler, Hamza Kaya; Çetin, Merve; Ünlügüzel, Benhur; Tezel, Başak (Academician Publishing Book DOI Portal, 2024)
-